The Ideational Metafunction Realisation of Indonesia’s President Prabowo Subianto’s Speech on Commemoration of National Teacher’s Day 2024 - Parasian, Nehemia Anugrah; Nurlela, N; Thyrhaya Zein, T.; Deliana, D (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
The ideational metafunction is one of the main concepts in Halliday’s Systemic Functional Linguistics (SFL), which explains how language represents human experience. This study focuses on the experiential function in President Prabowo Subianto’s speech delivered during the Commemoration of National Teacher’s Day 2024. A qualitative method was employed by analyzing the speech text using the transitivity system to identify processes, participants, and circumstances. The analysis revealed that material processes were predominantly emphasize concrete government actions and educational reforms, portraying the President’s commitment to improving teachers’ welfare and national education quality. The mental processes express empathy and appreciation for teachers, highlighting their dedication and emotional strength in shaping the nation’s future. Meanwhile, the relational processes establish teachers as the moral and intellectual pillars of national development, while extent circumstances reflect the wide scope of the intended policies. These results suggest that the speech highlights the government’s commitment to educational reform and teacher welfare through real and measurable actions. The findings provide new insights into the construction of political discourse in Indonesia and demonstrate how the ideational metafunction serves as a tool to convey ideological positioning in presidential communication. This study contributes to the field of political discourse analysis by providing a functional linguistic perspective on how ideational meanings are constructed in presidential speeches, particularly within Indonesia’s educational context.